1990
DOI: 10.1007/bf00965747
|View full text |Cite
|
Sign up to set email alerts
|

Brain development:1H magnetic resonance spectroscopy of rat brain extracts compared with chromatographic methods

Abstract: We compared in vitro 1H magnetic resonance spectroscopy (MRS) measurements of rat brain extracts (rats: 2-56 days old) with chromatographic measurements and in a further step also with results of in vitro MRS. The following substances can be reliably measured in brain extracts by in vitro MRS: N-acetylaspartate (NAA), total creatine (Cr), phosphorylethanoloamine (PE), taurine (Tau), glutamate (Glu), glutamine (Gln), gamma-aminobutyrate (GABA) and alanine (Ala). Two different methods of MRS data evaluation comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 28 publications
7
43
0
1
Order By: Relevance
“…It is a postulated source of acetate for lipid and myelin synthesis of oligodendrocytes (Satrustegui et al, 2007). As the immature rat brain develops, rapid increases in NAA are detected during the time of peak myelination (D'Adamo and Yatsu, 1966;Bates et al, 1989;Burri et al, 1990). Using purified rat brain mitochondria (Patel and Clark, 1979), the synthesis and transport of NAA out of mitochondria increased with brain development in concert with myelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a postulated source of acetate for lipid and myelin synthesis of oligodendrocytes (Satrustegui et al, 2007). As the immature rat brain develops, rapid increases in NAA are detected during the time of peak myelination (D'Adamo and Yatsu, 1966;Bates et al, 1989;Burri et al, 1990). Using purified rat brain mitochondria (Patel and Clark, 1979), the synthesis and transport of NAA out of mitochondria increased with brain development in concert with myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of both NAA and lactate were made using creatine as a reference, as total creatine (creatine ϩ phosphocreatine) is relatively constant in the brain after injury (Yeo et al, 2006) and during rat brain development (Burri et al, 1990). At 4 h after TBI ( Fig.…”
Section: N-acetyl-aspartate and Lactate Relationshipmentioning
confidence: 99%
“…In vitro MRS studies of NAA responses to osmotic stress-MRS has been reported to be an accurate method for measuring brain metabolite concentrations in vitro (Burri et al, 1990). These methods often employ extraction of solutes from tissues with perchloric acid, and subsequent analysis of the recovered metabolites by MRS. One study using MRS to detect metabolite concentrations in perchloric acid extracts from brain slices have shown a 60% decrease in NAA concentrations after hypo-osmotic shock (Bothwell et al, 2001).…”
Section: 31mentioning
confidence: 99%
“…Like for lactate, with which it is in equilibrium though pyruvate, conflicting observations were reported for alanine concentrations in the developing rat brain (Bayer and McMurray, 1967;Burri et al, 1990;Tkáč et al, 2003). However, both in vivo and in vitro studies in mice demonstrated that cerebral alanine content is higher at birth and decreases during development (Kulak et al, 2010;Yao et al, 1999), reflecting the high protein turnover in the developing brain as result of cell proliferation and tissue expansion.…”
Section: Energy Metabolismmentioning
confidence: 99%